The fish drying industry and its role in the development of Barangay Old Sagay, New Sagay Negros Occidental (1948-1994) - Gasataya, Daisie
When industries of Negros Occidental are the issue, what comes to mind is the agricultural product of sugarcane. The popularity of this industry has put other industries in lesses importance. Fishing, the second major industry, together with the complementary industries, was neglected for many years aspecially during the height of sugarcane industry in Negros Occidental despite the fact that the island seashore are primarily fishing villages. Old Sagay, located in the northmost town of Negraos Occidenatal is a fishing village. It became a Bargy. In 1946 when the twon site was moved from Old Sagay to Dalusan now officially called New Sagay. The prime products were fresh and dried fish. The period aftyer the war until the middle of 1950s was considered by the Brgy people as the ?awareness stage?. It was in 1948 that fish drying was established in the Barangay. In the 1950?s the people of Old Sagay started to indulge in the fish drying industry. Their interest was motivated by the industry because of a great supply of fish from the bountiful catch of the ?Iwag? and ?sunshine? fishing vessels. The barangay people saw the economic implication of the industry and therefore, a favorable response to the established industry in the place was inevitable. From the abundant catch ao ?iwag and sunshine? the people resorted to to drying fishes; thus the industry was established plus the fact that some individuals invested capitals in volume production of dried fish products. Dried fish producers during the late 60?s until the 70?s decreased their volume of production. Thius started the decline of both fishing and fish drying industry. The decline was called the ?small production stage? in whish the amount of fresh fish for drying was no longer bountiful. A yard was enough to bwe used as a working area and even drying yard this 1990?s. Inspite of some drawbacks, fishing and fish drying industry remain as part of the major industries in Sagay, Negros Occidental with sugar industry as the major one based on the economic profile of New Sagay. Thus, fishing and fish drying indurties are continuing business undertaking for some people in Old Sagay and the town of New Sagay, Negros Occidental, een in the 1990?s.